2011
DOI: 10.1245/s10434-011-2156-7
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging in Pancreatic Cancer: A Matched Analysis of Patients Resected Following Systemic Treatment of Initially Locally Unresectable Disease

Abstract: In this study, patients who were able to undergo resection following treatment of initial stage III pancreatic cancer experienced survival similar to those who were initially resectable. Resection is indicated in this highly select group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…This therapeutic goal is of importance, as a previous study by our group has suggested that patients who are able to undergo resection following initial systemic treatment of stage III disease experience similar survival to those whose tumors are initially resected 5 . Within the current study, 31% of patients initially deemed unresectable eventually underwent resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This therapeutic goal is of importance, as a previous study by our group has suggested that patients who are able to undergo resection following initial systemic treatment of stage III disease experience similar survival to those whose tumors are initially resected 5 . Within the current study, 31% of patients initially deemed unresectable eventually underwent resection.…”
Section: Discussionmentioning
confidence: 99%
“…Objective response rate(ORR) was defined as the percentage of patients who had a decrease >30% in the greatest dimension of the primary tumor or complete disappearance of the primary tumor. Pathologic response was also recorded, and the guidelines utilized for determining this response have been previously reported 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many improvements in chemotherapy and radiation therapy have been made, pancreaticoduodenectomy (PD or Whipple's procedure) remains the only chance for a cure and the standard of care for resectable pancreatic head adenocarcinoma. In patients with borderline resectable or locally advanced pancreatic cancer, curative surgical resection can be achieved after neoadjuvant chemotherapy and/or chemoradiation in the case of downstaging 2 . Unlike in historic series, PD has become a safer procedure with an important decrease in mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…4 Complete surgical resection remains the best option for meaningful patient survival; however, only about 20% of patients who present with PDAC are candidates for resection. 4 Complete surgical resection remains the best option for meaningful patient survival; however, only about 20% of patients who present with PDAC are candidates for resection.…”
mentioning
confidence: 99%